2006
DOI: 10.1111/j.1471-4159.2005.03599.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1 beta‐induced expression of the prostaglandin E2‐receptor subtype EP3 in U373 astrocytoma cells depends on protein kinase C and nuclear factor‐kappaB

Abstract: Both interleukin-1b (IL-1b) and prostaglandins (PGs) are important mediators of physiological and pathophysiological processes in the brain. PGE 2 exerts its effects by binding to four different types of PGE 2 receptors named EP1-EP4. EP3 has found to be expressed in neurons, whereas expression of EP3 in glial cells has not been reported in the brain yet. Here we describe IL-1b-induced EP3 receptor expression in human astrocytoma cells, primary astrocytes of rat and human origin and in rat brain. Using western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 77 publications
(154 reference statements)
0
21
0
Order By: Relevance
“…1A). Four PGE2 receptors have been identified in astrocytes (Fiebich et al, 2001;Waschbisch et al, 2006). To assess which receptor plays a potent role in the PGE2-induced CEBPD activation in astrocytes, four selective agonists of each EP subtype [ONO-DI-004 (DI-004) for EP1, ONO-AE1-259 (AE1-259) for EP2, ONO-AE-248 (AE-248) for EP3 and ONO-AE1-329 (AE1-329) for EP4] were used to treat U373MG cells.…”
Section: Pge2 Activates Cebpd Expression Through the Ep4 Receptor In mentioning
confidence: 98%
“…1A). Four PGE2 receptors have been identified in astrocytes (Fiebich et al, 2001;Waschbisch et al, 2006). To assess which receptor plays a potent role in the PGE2-induced CEBPD activation in astrocytes, four selective agonists of each EP subtype [ONO-DI-004 (DI-004) for EP1, ONO-AE1-259 (AE1-259) for EP2, ONO-AE-248 (AE-248) for EP3 and ONO-AE1-329 (AE1-329) for EP4] were used to treat U373MG cells.…”
Section: Pge2 Activates Cebpd Expression Through the Ep4 Receptor In mentioning
confidence: 98%
“…These results indicate that the EP3 receptor is locally induced by KA in hippocampal astrocytes, which may receive PGE 2 from endothelial cells. Preceding publications have already shown that EP3 mRNA is expressed in cultured astrocytes [34], and EP3 protein is induced in astrocytomas by interleukin-1β [35]. These findings indicate that astrocytic EP3 receptors may be upregulated under pathological conditions, and endothelial PGE 2 may directly activate EP3 receptors on astrocytic end-feet, not distant neuronal EP receptors in neurotoxic brain diseases, such as epileptic seizures.…”
Section: Mechanism For Exacerbation Of Neuronal Damage By Endothelmentioning
confidence: 87%
“…The size of the EP 3 receptor has been reported as low as 33-38 kD in splice variants [28,29] while the full length protein determined by amino acid comparison is estimated at ~55-63 kD. There are two sites of possible N-linked glycosylation, which can yield products of 65-75 kD that have been previously detected on Western blots [28,29]. Together these results suggest that constrictive effects of PGE 1 and PGE 2 are mediated at least in part by EP 3 receptors.…”
Section: 0 Discussionmentioning
confidence: 99%
“…EP 2 & 4 receptor subtypes have been shown to exist in chicken by molecular cloning [35], and our data support the existence of EP 3 receptors in the developing CAM (Fig 12). EP 3 receptors mediate contraction of the uterus, inhibition of gastric acid secretion, modulation of neurotransmitters, lipolysis, sodium and water reabsorption in kidney tubules and secretion of catecholamines [4,25,29,36-38]. The vasoactive effects of PGEs on pulmonary arteries appear to depend upon a variety of factors including the state of activation of the vascular smooth muscle prior to exposure to the lipid, whether the vessels are arteries or veins and/or the subtype of EP receptor expressed.…”
Section: 0 Discussionmentioning
confidence: 99%